Impact of Brand Experience and Brand Image on Outlet Satisfaction with Energizer Battery Brand - Hilal, Nur; R. Djatola, Hariyanto R. (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to examine the influence of brand experience and brand image on outlet satisfaction with the Betarai Energizer brand. The analytical method used is multiple regression analysis with SPSS 23 software in testing hypotheses that have previously been formulated in the problem statement. The research results show that brand experience and brand image have a positive effect on brand satisfaction. Brand experience has a greater influence than brand image on brand satisfaction. This shows that a positive brand experience can increase consumer brand satisfaction more than a positive brand image. Research implications Positive brand experiences and a strong brand image can help increase consumer brand satisfaction and can be important assets for companies in winning market competition. However, it is important to remember that brand experience and brand image must be managed consistently and continuously to maintain consumer brand satisfaction.